MULTILEVEL SYSTEM OF MEDICAL CARE TO CHILDREN’S POPULATION - A. A. Baranov; V. Yu. Al'bitskii; R. N. Terletskaya; D. I. Zelinskaya (Вопросы современной педиатрии, 2014)
The characteristic of multilevel system of medical care is given to the population of economically developed countries (preventive, patronage and hospital stages). Advantages in improvement of quality and availability of medical services are noted it. Information on the first experience of the organization of three-level medical care to the population is provided in the Russian Federation. Features of the organization of this system of medical care for children are discussed. Prime measures for introduction of three-level system of rendering different types of medical care in pediatric practice are offered. Need of development of accurate concepts of three-level medical care is noted: definition that such «three-level system» and «three-level approach», what sign (territoriality, property, contingent, type of the help, help specialization, etc.) will be cornerstone of reference of establishment and/or a type of the help to this or that level. It is obviously important to designate main objectives and problems of each level of medical care. Only on the basis of this basic approach to introduction of the three-level organization of medical care in subjects of the Russian Federation realization of the forthcoming stage of modernization of health care taking into account regional specifics and smallest losses both for the population, and for medical workers is possible.